2017
DOI: 10.1177/0300060517705540
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of glycine powder air-polishing combined with scaling and root planing in the treatment of periodontitis and halitosis: A randomised clinical study

Abstract: IntroductionThis study was performed to evaluate the clinical efficacy of using the Perio-Flow device (Electro Medical Systems, Nyon, Switzerland) adjunctively with mechanical instrumentation on periodontal parameters and halitosis.Materials and MethodsSixty patients who presented with a 4- to 6-mm probing pocket depth were recruited for the study. Patients were randomly assigned to scaling and root planing (SRP) or SRP + glycine powder air-polishing (GPAP). For both groups, the plaque index, gingival index, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
(33 reference statements)
1
27
0
1
Order By: Relevance
“…Air-polishing with the abrasive glycin powder for 10 seconds per periodontal pocket as an adjunctive mean for the SI in the initial therapy of periodontitis did not lead to clinical bene ts at plaque and gingival indices, probing depth, bleeding on probing and attachment level 30 days after the treatment when compared with SI only [13]. Tsang et al [27] found no signi cant differences for biomarkers after adjunctive air-polishing at SI in untreated periodontitis patients during the study period of six months.…”
Section: Discussionmentioning
confidence: 86%
“…Air-polishing with the abrasive glycin powder for 10 seconds per periodontal pocket as an adjunctive mean for the SI in the initial therapy of periodontitis did not lead to clinical bene ts at plaque and gingival indices, probing depth, bleeding on probing and attachment level 30 days after the treatment when compared with SI only [13]. Tsang et al [27] found no signi cant differences for biomarkers after adjunctive air-polishing at SI in untreated periodontitis patients during the study period of six months.…”
Section: Discussionmentioning
confidence: 86%
“…Wennström et al (2011) reported no signi cant differences of clinical variables between the use of ultrasonic instruments and air polishing with glycine powder and the nozzle device in maintenance patients during the study period of 60 days. Air-polishing with the abrasive glycin powder for 10 seconds per periodontal pocket as an adjunctive mean for the SI in the initial therapy of periodontitis did not lead to clinical bene ts at plaque and gingival indices, probing depth, bleeding on probing and attachment level 30 days after the treatment when compared with SI only (Caygur et al 2017). Tsang et al (2018) found no signi cant differences for biomarkers after adjunctive air-polishing at SI in untreated periodontitis patients during the study period of six months.…”
Section: Discussionmentioning
confidence: 88%
“…Rövid, 7 napos kontroll alapján Möene, 2 hónapos visszarendelési periódus szerint Wennström, míg hosszú, 12 hónapos időintervallumban Müller nem talált különbséget az air-abrazív és a hagyományos subgingivális debrimentálást összehasonlítva 4 mm-es vagy mélyebb kiindulási tasakmélység értékek esetében [12,14,27]. Caygur és munkatársai az additív hatást vizsgálta rövid időintervallumban (7-14-30 nap), közepesen mély tasakok (4-6 mm) terápiája során nem talált pozitív hatást a teszt csoportnál, ahol a hagyományos gyökérfelszín-simítást követően gly cinporral levegőabráziós kezelést is végeztek [28]. Kargas 3 mm-nél mélyebb kiindulási értékeknél, 3 és 6 hónapos kontrollidő alapján, rosszabb eredményeket kapott a glycinporral végzett kezelések esetében.…”
Section: Megbeszélésunclassified